Pengaruh Tekanan Anggaran Waktu, Tekanan Ketaatan, dan Pengalaman Auditor Terhadap Audit Judgment (Studi Pada Kantor Akuntan Publik Provinsi Daerah Istimewa Yogyakarta) - Tiar Rizky Abdillah; Edi Joko Setyadi; Suryo Budi Santoso; Rina Mudjiyanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
This study aims to examine the effect of time budget pressure, obedience pressure, and auditor experience on audit judgment to auditors in Public Accounting Firm of Yogyakarta as partially. The population are the auditors who works at Public Accounting Firm of Yogyakarta. Sampling method in this research using purposive sampling with criterion of senior auditor and junior auditor. Data analysis technique used is multiple linear regression analysis method with significant level (α) 0.05. The questionnaire used in this study was 35 out of 38 questionnaires. The results of this study indicate that the time budget pressure negatively affect on audit judgment,while the obedience pressure and auditor experience have a significant positive effect on audit judgment.